Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4049/jimmunol.0901509
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Inhibition of MEK–ERK Signaling Enhances Th17 Differentiation

Abstract: The cytokines and transcription factors that promote Th17 cell development have been extensively studied. However, the signaling pathways that antagonize Th17 differentiation remain poorly characterized. In this study, we report that pharmacologic inhibition of MEK–ERK signaling enhances the in vitro differentiation of Th17 cells and increases their gene expression of il-17a, il-17f, il-21, il-22, and il-23r. IL-2, which suppresses Th17 differentiation via STAT5 activation, also acts through ERK signaling to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 47 publications
(48 reference statements)
3
38
2
Order By: Relevance
“…Nevertheless, the roles of ERK signaling in the regulation of Th17 development have become controversial. Inhibition of ERK in T cells by U0126 was reported to promote Th17 cell development under Th17 conditions (54). In contrast, a recent study by Liu et al (24) demonstrated that blockage of T cell-intrinsic ERK signaling, using ERK inhibitor PD98059 or U0126, leads to reduced Th17 responses.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, the roles of ERK signaling in the regulation of Th17 development have become controversial. Inhibition of ERK in T cells by U0126 was reported to promote Th17 cell development under Th17 conditions (54). In contrast, a recent study by Liu et al (24) demonstrated that blockage of T cell-intrinsic ERK signaling, using ERK inhibitor PD98059 or U0126, leads to reduced Th17 responses.…”
Section: Discussionmentioning
confidence: 79%
“…S4h,i). Of note, Erk1/2 inhibition has been previously shown to enhance Th17 cell differentiation (Tan and Lam, 2010) and Erk1/2 phosphorylation has been linked to the reduced expression of REV-ERB proteins (Castellano et al, 2014; Kojetin and Burris, 2014), but the mechanism involved and its relevance for T cells has not been characterized yet. Through a bioinformatic analysis of the nr1d1 promoter we identified a binding site for the CAAT/enhancer-binding protein α (C/EBPα), a leucine zipper transcription factor involved in the regulation of cellular differentiation (Lekstrom-Himes and Xanthopoulos, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…One group has reported that the p38 and JNK pathway is important for IL-17A production, based on experiments with pharmacological inhibitors (Lu et al, 2010). Another group has reported that the ERK pathway negatively regulates IL-17A production (Tan and Lam, 2010). Furthermore, it has been reported that JNK1-deficient (Mapk8 À/À ) mice were resistant to EAE (Tran et al, 2006).…”
Section: Discussionmentioning
confidence: 97%